Synthesis of Novel Bioactive Lipophilic Hydroxyalkyl Esters and Diesters Based on Hydroxyphenylacetic Acids - Andrea Fochetti; Noemi Villanova; Andrea Lombardi; Veronica Lelli; Yuri Gazzilli; Anna Maria Timperio; Giancarlo Fabrizi; Roberta Bernini (Molecules)
Novel lipophilic hydroxyalkyl esters were synthetized by Fischer esterification in good to excellent yields (60–96%) from a panel of hydroxyphenylacetic acids and increasing chain length (2 to 8 carbon atoms) α,ω-diols. The in vitro antioxidant activity of these compounds was evaluated by DPPH and ABTS assays. Hydroxybutyl esters and hydroxyphenylacetic acids were used as starting materials for the synthesis of novel lipophilic diesters (butyl diarylacetates) using Mitsunobu reaction. The final products were isolated in moderate to good yields (40–78%), and their structure–antioxidant activity relationships are discussed. Compounds bearing the catechol moiety on one of the two aromatic rings and high lipophilicity proved to be the strongest antioxidants and were selected for testing as antibacterials against Staphylococcus aureus and Escherichia coli, obtaining preliminary and promising results.